Light and electron microscopic localization of calcitonin gene-related peptide immunoreactivity in lamina II of the feline trigeminal pars caudalis/medullary dorsal horn: a qualitative study - Henry, M A; Nousek-Goebl, N A; Westrum, L E (Synapse (New York, N.Y.), 1993)
Calcitonin gene-related peptide (CGRP) is a neuropeptide that is associated with a subset of primary afferent fibers and appears to have a role in nociception. The purpose of the present study was to perform a qualitative light, and especially electron microscopic (LM and EM), examination of CGRP-immunoreactivity (IR) within lamina II (substantia gelatinosa) of the feline pars caudalis/medullary dorsal horn (PC/MDH) of the spinal trigeminal nucleus. The LM investigation revealed massive CGRP-IR within lamina II outer, with fewer fibers that traversed lamina II inner. The EM preparations showed CGRP-IR in small, thinly myelinated and unmyelinated axons, preterminal axons, and in axon terminals that formed asymmetric synaptic contacts onto small dendritic profiles. The terminals with CGRP-IR were often the central element within glomeruli, where the terminal usually formed 2 or more asymmetric synaptic specializations onto 1 or more dendrites. Many of these postsynaptic dendrites contained synaptic vesicles. Other profiles were seen forming presynaptic contacts onto the terminal with CGRP-IR, and these profiles most likely represent presynaptic dendrites and/or other axon terminals of intrinsic origin. The synaptic association of terminals showing CGRP-IR with vesicle-containing dendrites, presynaptic dendrites, and/or other axon terminals suggests that terminals with CGRP-IR are especially susceptible to modulation.